GAMBARAN KOMITMEN PROFESI GURU SEKOLAH X - Maria Dwi Yanika Hesti Nugraha (Psibernetika, 2011)
Century 21 is known as the knowledge century, an era by setting a particular specification for the human resources that give great influence to the world of education. At a school organization, people or human resources is an important element, in this case is the teacher. Competency of teachers will be increased according to increase teachers' commitment to the profession. Therefore, it is important as an educational institution (school organization) to be able to create the conditions of school organization that is able to strengthen the commitment of the teaching profession. Commitment of the teaching profession was measured using a questionnaire adopted from Situmorang (2000) based on the characteristics of the professional commitment of teachers in the opinion of Meyer and Allen (in Steers, 1985). Subjects in this study were from the population of teachers in school X. The sample in this study are the organization of kindergarten teachers, elementary and junior high, East Jakarta, as many as 84 teachers. These results indicate that the picture of affective commitment to the profession is very high. Keywords : commitment, komitmen profesi, teacher